ORIGINAL PAPERExercise h-FABP plasma concentration in healthy subjects - Małek, Łukasz A.; Grabowski, Marcin; Szpotańska, Monika; Śpiewak, Mateusz; Główczyńska, Renata; Filipiak, Krzysztof J.; Opolski, Grzegorz (Archives of Medical Science, 2005)
Introduction: Heart fatty acid binding protein (h-FABP) is considered a heart specific marker of necrosis, but it is also present in the skeletal muscles. The aim of the study is to check whether h-FABP plasma concentration increases in healthy subjects after exercise. Material and methods: Plasma h-FABP concentrations were measured in 16 healthy men and 3 healthy women (mean age 24) before and after their participation in the 11 kilometer-long marathon – XVI Independent Race in Warsaw by means of a point-of-care semi-quantitative test. Results: All 19 runners had a negative result of the pre-run h-FABP test (<7 µg/l). Out of eighteen runners who finished the race: 9 (50%) presented with a positive result of the point-of-care test, 7 runners (39%) had a negative result and in 2 participants the test showed invalid results. All studied subjects were free of cardiologic risk factors, recent infections and were not on any medication. All positive results were found among the male subjects. Discussion: Plasma h-FABP can increase after moderate exercise probably due to skeletal muscle injury. The concentrations observed after moderate exercise are generally lower than those reported for the acute myocardial infarction. Conclusion: The point-of-care h-FABP test might be therefore useful in the diagnosis of myocardial necrosis in subjects with angina pectoris and exercise induced chest pain.